Preparation and Characterization of Ternary Poly(arylene ether sulfone) Nanofibrous Membranes Via Soultion-blowing with Phthalein Group in the Main Chain - Song, Guocheng; Li, Jing; Zhu, Jing; Yu, Junrong; Wang, Yan; Hu, Zuming (Current Nanoscience, 2018)
Background: As a new type of micron/nanofiber preparation technology, solutionblowing has attracted more and more attention and applied in wide application field. Compared with electrospinning, it has such advantages as simple equipment, easy accessibility and low energy consumption. Objective: In this paper, the modified poly(arylene ether sulfone) polymers are expected to be prepared and converted into nanofibers via solution-blowing technology, and can be applied in microfiltration and oil-water separation. Methods: We synthesized a series of linear high molecular weight ternary poly(arylene ether sulfone) via adding different content of phthalein group, and then successfully fabricated the corresponding nanofibers via solution-blowing technology. The concentration of spinning solution was optimized to obtain the uniform and smooth nanofibers. The membranes were characterized by Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Wide-angle X-ray diffraction (WAXD), Differential scanning calorimetry (DSC), Thermogravimetric analysis (TGA), and Water contact angle (WCA), etc. Furthermore, the filtration experiment and oil-water separation test were executed to verify the membranes practical application value. Results: The results showed the spinning solution with polymers concentration of 25 wt% was suitable to prepare nanofibers with well appearance and the membranes had a higher glass transition temperature (Tg) and better thermal stability with the increase content of phthalein groups. The oil-water separation experiments of membranes showed fast and efficient separation ability for oil-water mixtures at special scale. Conclusion: The nanofibrous membranes of modified poly (arylene ether sulfone) with cardo group in the main chain were successfully prepared via solution-blowing technology and exhibited great application potential in microfiltration.
Keywords: Poly(arylene ether sulfone)d&gt